Effect of moringa leaf powder and agave inulin on performance, intestinal morphology, and meat yield of broiler chickens - Yaritza Moreno-Mendoza; Karla Denisse López-Villarreal; Carlos Alberto Hernández-Martínez; Luis Edgar Rodríguez-Tovar; Ana Cecilia Hernández-Coronado; Adolfo Soto-Domínguez; Michael E. Hume; Gerardo Méndez-Zamora (Poultry Science, 2021)
The addition prebiotics in broiler diets can benefit digestion and nutrient abortion. The objective of the present study was to evaluate the effects of moringa leaf powder and agave inulin on growth performance, intestinal morphology, and slaughter traits of broiler chickens over 40 d of grow-out. A total of 280 broilers (Ross 308) aged 1 d were randomly allocated to 4 treatments, with 7 replicates each and 10 chicks per replicate: T1 = control diet, T2 = control diet with 15 g/kg of moringa leaf powder, T3 = control diet with 15 g/kg of agave inulin, and T4 = control diet with 15 g/kg of moringa leaf powder and 15 g/kg of agave inulin. The results showed that analysis of treatments at time were not different (P > 0.05) for broiler weights, feed and water intake, and weight gain. Treatment was significant (P < 0.05) for feed efficiency at 22 to 40 d; the T4 group presented higher (P < 0.05) values, and the T1 group presented lower (P < 0.05) values. However, the villus lengths of intestinal sections were different (P < 0.05) among treatments. In the duodenum, jejunum, and ileum, villus lengths were highest (P < 0.05) in the T2 group and lowest (P < 0.05) in the T3 and T4 groups. Villus widths in the duodenum and ileum were highest (P < 0.05) in the T2 group, but the T1 group showed highest (P < 0.05) values in the jejunum sections. The T3 and T4 groups showed lowest (P < 0.05) values in villus width in the duodenum, jejunum, and ileum. Thigh yield was highest (P < 0.05) in the T2 group and lowest (P < 0.05) in the T4 group. The T1 group exhibited the highest (P < 0.05) piece yields for leg, wing, and hip-back. The T4 group showed lowest (P < 0.05) leg and wing yields. Moringa leaf powder and agave inulin at a concentration of 15 g/kg in diets did not affect broiler performance, whereas moringa leaf powder improved intestinal morphology and thigh yield, and agave inulin improved leg yield. The results demonstrated benefits of these 2 feed additives to improve intestine health and meat yield in broilers over a 40-day grow-out.